Influence of Various Precursor Compositions and Substrate Angles on ZnO Nanorod Morphology Growth by Aqueous Solution Method - Puenisara Limnonthakul; Daw Yangnoi; Patamas Bintachitt; Manoch Hengwattana; Mati Horprathum (Institute for Research and Community Services (LPPM) ITB, 2016)
ZnO nanorods were synthesized on silicon wafer substrate with a seed zinc layer using the aqueous solution method. The influence of various precursor compositions on the morphology of the ZnO nanorods, with substrate angles at 0° and 90°, was investigated. The various ratios of hexamethylenetetramine in zinc nitrate hexahydrate were used as precursors in the synthesis of ZnO. Scanning electron micrography indicated that the growth of the ZnO nanorods with a 0° substrate angle was smaller than with a 90° substrate angle. The substrate angle is defined as the angle between the plane of the substrate and the horizontal layer of an aqueous solution. When the precursor concentration of hexamethylenetetramine is not equal to the ratio corresponding to the chemical reaction, the effect of the substrate angle on the diameter size and morphology of the ZnO nanorods is evident. Grazing incident X-ray diffraction (GIXRD) was used to characterize the structure of all samples. The diffraction patterns showed that the orientation matched the hexagonal wurtzite structure.